The European Union trade, development and cooperation agreement (TDCA) with South Africa : promoting development or self interest? - Mavura, Mike Tigere (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2007)
This research analyses development cooperation between the European Union (EU) and South Africa with the objective of determining which between the two entities, ultimately benefits more out of this arrangement The research goes beyond the altruistic reasons offered by the EU as the rationale for development cooperation to investigate whether South Africa's development is actually being promoted by this cooperation. Further, the research investigates whether there is also EU self-interest that informs this development cooperation. This research is conceptualised within the development aid debate framework. The research argues that this development cooperation is important to South Africa even though its impact is in real terms has not been extensive due to a number of factors. It further contends that there are EU political, security and economic interests amongst others that are being promoted by this development cooperation. The research concludes by asserting that this development cooperation promotes the mutual interests of the EU and South Africa. This conclusion challenges the paradigms of the debate on development aid which is premised in black and white terms of development aid promoting either donor or recipient interests.
Keywords: European Union; Economic development -- South Africa; European Union countries -- Foreign economic relations -- South Africa; South Africa -- Foreign economic relations -- European Union countries